Социально-экономическое развитие южнороссийской окраины в конце ХIХ – начале ХХ вв. (на материалах Северного Кавказа) - Суханова, Н.И. (Історичний архів. Наукові студії, 2014)
Проанализировано процессы социально-экономического развития Северного Кавказа
в конце ХIХ – начале ХХ вв. В ходе анализа выявлено общие и особенные черты
развития собственно Российской империи и одной из ее южных окраин – Северного
Кавказа. Характерной чертой развития региона в исследуемое время было сочетание
традиционализма и модернизационных перемен, вызванных влиянием российского
капитализма. Проаналізовано процеси соціально-економічного розвитку Північного Кавказу
наприкінці ХIХ – на початку ХХ ст. У ході аналізу виявлено загальні та особливі риси
розвитку власне Російської імперії і однієї з її південних околиць – Північного Кавказу.
Характерною рисою розвитку регіону в досліджуваний час було поєднання
традиціоналізму та модернізаційних змін, викликаних впливом російського капіталізму. The article analyses the processes of socio-economic development of the Northern
Caucasus in the late 19th and early 20th centuries. The analysis identified General and specific
features of the Russian Empire and one of its southern suburbs to the North Caucasus. A
characteristic feature of the region’s development was analyzed in combination of traditionalism
and modernization changes caused by the influence of Russian capitalism. The economic
profile of the region was quite diverse: from handicraft and primitive agriculture to farm farming
and nascent industry. Despite the ethnic and social diversity of the population of the region,
while maintaining the potential energy of the conflict, here for the long years of cohabitation of
different ethnic groups and social groups developed the algorithm for the conservation of
interaction and interpenetration of economic-cultural traditions. The local population is always
knew the price of conflict, therefore retained the possibility of peace traditions of conflict
resolution. All these factors have played a stabilizing role in the North Caucasus and create
conditions of its active integration into the capitalist forms of management.